Effects of Incentives for Renewable Energy in Colombia (2017)
ABSTRACT:Introduction: This paper studies the potential effects of a new regulation to promote the development of renewable energy technologies in Colombia. Methods: This work establishes a methodology to include the effects of tax incentives in the calculation of the Levelized Cost of Electricity (LCOE). Two incentives are analyzed: tax deductions on the investment and accelerated depreciation on assets. Results: The first calculation shows up to 20% reduction in the LCOE; unfortunately, the regulation restricts small or new business from applying for all incentives. For this reason, two complementary mechanisms are proposed to allow small business ventures, such as forest biomass projects, to apply for incentives. As a result, a 30% reduction in the LCOE is obtained for photovoltaics (PV) and 15% for forest biomass. Conclusions: The deducted tax factor permits the direct computation of a tax-adjusted LCOE, avoiding extensive cash flow calculations. The high potential of biomass resources in Colombia and the proposed mechanisms can push LCOE prices lower than the grid parity cost in most isolated regions. This represents a great opportunity in Colombia because of the huge amount of biomass resources and the potential to create new job opportunities.